Recurrent diffuse large B-cell lymphoma mimicking primary breast cancer - Bastos, David Caetano; Lima, Eduardo Nóbrega Pereira; Bitencourt, Almir Galvão Vieira; Barbosa, Paula Nicole Vieira Pinto (Mastology, 2021)
Breast lymphoma can represent 0.8%–2.2% of extranodal lymphomas and 0.1%–0.5% of primary breast neoplasms. Imaging findings are not specific, and its distinction from primary invasive breast carcinoma should be based on clinical data and histopathological analysis. We present the case of a 62-year-old woman who showed an unusual pattern of recurrent diffuse large B-cell lymphoma (DLBCL) mimicking primary breast cancer on imaging studies, including mammography, ultrasound, magnetic resonance imaging (MRI), and positron emission tomography-computed tomography (PET-CT).